PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASI PEGAWAI NEGERI SIPIL PADA DINAS PENDIDIKAN DAN UPTD DINAS PENDIDIKAN KABUPATEN INDRAGIRI HULU - Rachmat Supriyanto Sinaga; Sri Indarti; Marzolina Marzolina (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
This study aims to determine The Effect Of Leadership and Motivation to Job Satisfaction and Organizational Commitment Civil Servants At the Department of Education and UPTD Indragiri Hulu. This study population is a Civil Servant amounted to 170 people, the determination of the number of samples by using the formula Slovin concordance rate of 5% using cluster random sampling and purposive sampling, a sample of 119 respondents. Data collection techniques used questionnaires and interviews. The analysis tool used is path analysis using SPSS 21 for windows. The results of this study indicate that: (1) leadership and no significant positive effect on job satisfaction civil servants. (2) Motivation positive and significant impact on job satisfaction civil servants. (3) Job satisfaction and no significant positive effect on organizational commitment of civil servants. (4) Leadership positive and significant effect on organizational commitment of civil servants. (5) Motivation positive and significant effect on organizational commitment of civil servants. (6) Leadership positive and significant impact indirectly on organizational commitment of civil servants through the mediating role of job satisfaction variables. (7) Motivation positive and significant impact indirectly on organizational commitment of civil servants through the mediating role of job satisfaction variables.